Polypharmacy among Geriatric People: Community Pharmacy based study in Bhaktapur district, Nepal - Chaudhary, Shrijana Kumari (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Polypharmacy among geriatric group is a major problem. Risk of an adverse effect increases exponentially with number of drugs used, partly because multiple drug therapy reflects the presence of many disease. The aim of this study was to assess the polypharmacy among geriatric people visiting community pharmacy of Bhaktapur district. Material and Methods: A prospective cross sectional study was conducted among 114 geriatric people (>60Years). The data collected from patients included: Socio-demographic details as age, gender, comorbid diseases, medication history. In this study, polypharmacy was considered as having > 5 medications per prescription. Medication appropriateness for patient was analyzed by applying, screening tool to alert to right treatment (START) and screening tool of older person’s prescription (STOPP) criteria. Results: Out of 114 geriatric patients 57.9% were male and 42.1% were female. Number of drugs prescribed to the patients were 634 with an average of 5.56 drugs per person. Cardiovascular drugs accounted for most (33.4%) followed by gastrointestinal tract drugs (11.5%), anti-diabetic drugs (10.89%). Over the counter drugs (OTC) were more common among geriatric, mainly proton pump inhibitor and non-steroid anti-inflammatory drugs. Depending upon the number of drugs, five and more than five drugs were consumed by single patients (n=73). Poly pharmacy can be seen among 64.03% geriatric patients. Potentially inappropriate medications were prescribed to 54 patients, overprescribing to38.5% and omission to 8.7% depending upon screening tool to alert to right treatment (START) and screening tool of older person’s prescription (STOPP) START. Conclusions: In this study polypharmacy was more common among geriatric group. Geriatric group were receiving around 64.03% polypharmacy, 47.3% inappropriate prescription and 33.3% using over the counter drugs.